2013
DOI: 10.1680/maen.2010.29
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of breakwater crown wall – calculation methods

Abstract: 2 3An investigation was undertaken consisting of a state-of-the-art and comparative analysis of currently available methods for calculating the structural stability of wave walls in sloping breakwaters. A total of six design schemes are addressed. The conditions under which the formulations and ranges of validity are explicitly indicated by their authors, are given. The lack of definition in parameters to be used and aspects not taken into account in their investigations are discussed and the results of this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Negro Valdecantos et al (2013) did a comparative analysis of currently available methods for calculating loads on structures in sloping breakwaters. The aim of this study was to analyse and compare existing wave wall calculation methods of: Iribarren and Nogales (1964), Gűnback and Gȍcke (1984), Bradbury and Allsop (1988), Pedersen (1996), Martin et al (1999) and Berenguer and Boanza (2006).…”
Section: Wave Load Calculation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Negro Valdecantos et al (2013) did a comparative analysis of currently available methods for calculating loads on structures in sloping breakwaters. The aim of this study was to analyse and compare existing wave wall calculation methods of: Iribarren and Nogales (1964), Gűnback and Gȍcke (1984), Bradbury and Allsop (1988), Pedersen (1996), Martin et al (1999) and Berenguer and Boanza (2006).…”
Section: Wave Load Calculation Methodsmentioning
confidence: 99%
“…To come to a final design additional tests on a physical model are recommended by Negro Valdecantos et al (2013). It is stated by Negro Valdecantos et al (2013), and confirmed by Braña and Gullén (2005), that Martin et al (1999) gives the best physical insight since it separately analyses the dynamic and quasi-static forces on the structure, whereas Pedersen (1996) is the most reliable method even outside the range of application. For that reason the method of Pedersen (1996) will be investigated within this research.…”
Section: Wave Load Calculation Methodsmentioning
confidence: 99%
“…The final paper, by Negro et al (2013), again concerns wave loading, this time on the crest or crown wall of a breakwater. In this case, extreme wind-wave loading is considered and a number of currently available design methods are briefly summarised before being tested against selected data sets as a basis for a critical review of the different methods.…”
Section: Maritime Engineeringmentioning
confidence: 99%
“…For example, a rate of q = 10 l/s per m implies significant overtopping for dikes, seawalls and embankments. (BSI, 1991) We have, in the first case, the study relating to pressure diagrams from Iribarren (Negro, 2013) There are different models of calculation of crown wall stability against the action of the incident waves. Most of them calculate pressures (Iribarren, Günbak, Martín and Berenguer) and forces (Bradbury and Pedersen) on the structure.…”
Section: Introductionmentioning
confidence: 99%